2003
DOI: 10.1002/gene.10169
|View full text |Cite
|
Sign up to set email alerts
|

Expression of conditional cre recombinase in epithelial tissues of transgenic mice

Abstract: Summary:Keratin 18 (K18) expression is a defining characteristic of internal epithelial cells of mammals. Here, we used the K18 gene and an internal ribosome entry site (IRES) to express green fluorescent protein, human placental alkaline phosphatase, and a modified Cre recombinase in an epithelial specific pattern in transgenic mice. The K18-driven alkaline phosphatase was expressed in liver, kidney, uterine endometrium, and other internal epithelia. The enzymatic activity of the Cre recombinasemutant estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Mammary fat pads were excised, mounted on glass slides, fixed in acidic ethanol (Carnoy's fixative or buffered formaldehyde), and stained with carmine alum overnight (23). For visualization of bacterial ␤-galactosidase, mammary tissues were fixed and stained as described previously (24). Apoptotic cells were identified with a commercial terminal deoxynucleotidyltransferase-mediated nick end labeling staining kit (Apotag kit; Intergen) according to the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Mammary fat pads were excised, mounted on glass slides, fixed in acidic ethanol (Carnoy's fixative or buffered formaldehyde), and stained with carmine alum overnight (23). For visualization of bacterial ␤-galactosidase, mammary tissues were fixed and stained as described previously (24). Apoptotic cells were identified with a commercial terminal deoxynucleotidyltransferase-mediated nick end labeling staining kit (Apotag kit; Intergen) according to the instructions of the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…In order to further define the role of epithelial ERa in the early prostatic development, the use of NKX3.1 Cre could be an ideal strategy, because its Cre activity begins to express at embryonic stage E17.5 in a prostatic epithelium-specific manner. 52 Alternatively, we could utilize other epithelial specific Cre mice, CK18-Cre and CK14-Cre, 53,54 to disrupt the ERa gene in the mouse prostate epithilium. In addition, Omoto et al 16 has shown that the expression of ERa is stage-dependent and its expression in the mouse prostate epithelial cells could be changed from negative to positive under different challenges, such as estrogenic compound exposure, 44 castration followed by androgen supplementation 16 and pathophysiological progression from normal prostate to benign prostatic hyperplasia or prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the transgenic line Y10-Cre, which induces recombination in the epithelial component of developing skin as early as embryonic day 14.5 (Vidal et al, 2005), the Brn4-Cre line, which primarily directs Cre expression to the neural tube but also shows ectopic Cre expression in the ventral epidermis (Ahn et al, 2001), the knockin line Krox-20-Cre, with expression in hair follicles in addition to the nervous system and bones (Gambardella et al, 2000;Voiculescu et al, 2000), the K18-CreER T2 lines, which have been reported to be active in the hair follicle (Wen et al, 2003) or have been employed to target Merkel cells (Van Keymeulen et al, 2009), and finally the K19-CreER T line (Means et al, 2008), which targets (in addition to the epithelial cells of several endodermal organs) hair follicle bulge stem cells (Lapouge et al, 2011).…”
Section: Cre Recombinase Mouse Linesmentioning
confidence: 99%